Inflammation in the CNS: Advancing the Field Using Intravital Imaging - Saparna Pai (Frontiers Research Topics, 2017)
Inflammation of the CNS can have devastating, long-lived, and in some cases fatal consequences for patients. The stimuli that can induce CNS inflammation are diverse, and include infectious agents, autoimmune responses against CNS-expressed antigens, and sterile inflammation following ischemia or traumatic injury. In these conditions, cells of the immune system play central roles in promulgation and resolution of the inflammatory response. However, the immunological mechanisms at work in these diverse responses differ according to the nature of the response. Our understanding of the actions of immune cells in the CNS has been restricted by the difficulty in visualising leukocytes as they undergo recruitment from the cerebral microvasculature and following their entry into the CNS parenchyma. However, advances in in vivo microscopy over the last 10-15 years have overcome many of these difficulties, and studies using these forms of microscopy have revealed a wealth of new information regarding the cellular and molecular mechanisms of CNS inflammation. This Research Topic brings together state of the art reviews examining the use of in vivo imaging in investigating inflammation and leukocyte behaviour in the CNS. Papers in this Research Topic describe how in vivo microscopy has increased our understanding of the actions of immune cells in the inflamed CNS, following various stimuli including autoimmunity, infection and sterile inflammation.